2020
DOI: 10.1080/13629395.2020.1822058
|View full text |Cite|
|
Sign up to set email alerts
|

Empowering a fragmented diaspora: Turkish immigrant organizations’ perceptions of and responses to Turkey’s diaspora engagement policy

Abstract: The existing literature on state-diaspora relations, primarily in the MENA, has mostly focused on how and why home states engage their diasporas, rather than with what consequences. This article investigates how different groups within the diaspora community are affected by the homeland's multi-tiered diaspora engagement policy. I argue that sending states influence select immigrant organizations' mobilization by empowering them in two key ways: They instil selfconfidence and collective identity in organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Nowadays, by contrast, there is an exchange of imams between these two organizations (Arkilic 2020). Back then, however, the integration of Turkey in the religious accommodation of people from Turkey and the promotion of transnational activities was in line with Germany's understanding of citizenship, which was based on ancestry (Koopmans and Statham 2003).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Nowadays, by contrast, there is an exchange of imams between these two organizations (Arkilic 2020). Back then, however, the integration of Turkey in the religious accommodation of people from Turkey and the promotion of transnational activities was in line with Germany's understanding of citizenship, which was based on ancestry (Koopmans and Statham 2003).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…20 On 31 October 2012, the AABK organized a mass protest in Berlin to oppose the AKP's Syria policy. 21 Even though the rift between Sunnis and Alevis had long existed under the previous Turkish governments, the members of the Alevi diaspora in Europe perceive the AKP government as more aggressive and threatening compared to other Turkish governments (Arkilic, 2016;Arkilic, 2020b). The FUAF's chairperson confirmed that the Sunni-Alevi divide has intensified under the AKP rule:…”
Section: The Transformation Of French Alevis' Relations With Their Ho...mentioning
confidence: 99%
“…Accordingly, the AKP's relations with Gülenaffiliated diaspora members and organizations have soured, rendering Gülenists in Europe the main enemy of the state. In the wake of the post-coup purge, Turkey has urged European policy-makers to shut down Gülen-linked institutions and to arrest or extradite Gülenists to Turkey, which has become an alarming source of tension between Turkey and European states (Arkilic 2020).…”
Section: A New Actor Takes the Stage: The Akp's Transformation Of Dommentioning
confidence: 99%
“…Alevi, Kurdish, secular, and Gülenist groups). Additionally, Turkey's bifurcated diaspora engagement policy has created tensions between the AKP government and European countries, which argue that Ankara's 'long arm' in the transnational space is detrimental to the Turkish community's integration prospects and acts a tool of foreign intervention (Arkilic 2020).…”
Section: Introductionmentioning
confidence: 99%